Advances in Nanocomposites Modeling, Characterization and Applications - Meguid, Shaker A. (Springer International Publishing : Imprint: Springer, 2016)
This book covers nanocomposite materials possessing a broad range of multifunctionality. It is intended to elucidate highly original developments from recent research and developments of these critical newly developed engineered materials, covering multiscale modeling, molecular dynamics, finite element method, atomistic based continuum, synthesis and characterization, condition health monitoring, spectroscopic characterization techniques, self-lubricating materials, and conducting polymers. It is a compilation of the recent efforts of some of the most eminent researchers in the world. Providing a range of perspectives from theory and applications, Advances in Nanocomposites: Modeling, Characterization Applications is ideal for engineers, physicists, and materials scientists in academia, defence organisations and industry.